Facile One-Step Fabrication of 1T-Phase-Rich Bimetallic CoFe Co-Doped MoS2 Nanoflower: Synergistic Engineering for Bi-Functional Water Splitting Electrocatalysis - Li, Xinyue; Song, Yahui; Huang, Yiming; Zhang, Jihui; Wu, Siyu; Zhang, Wentao; Wang, Jin; Zhang, Xian (Molecules (Basel, Switzerland), 2025)
MoS2 has emerged as a highly promising catalyst for the hydrogen evolution reaction (HER) owing to its exceptional catalytic properties. However, there is a pressing need to further enhance its reactivity and integrate oxygen evolution reaction (OER) capabilities to facilitate its industrial implementation. In this context, a dual-metal doping approach presents a straightforward and effective strategy to achieve superior catalytic performance. Systematic characterization and electrochemical evaluations reveal that the synergistic effects of Co and Fe doping significantly enhance both HER and OER activities, demonstrating remarkable potential for practical applications in energy conversion and storage systems. The unique flower-like architecture of the material endows it with a substantially enlarged surface area, which significantly increases the exposure of active sites and facilitates enhanced catalytic activity. Specifically, it achieves the low overpotentials of −127 and 292 mV at 10 mA cm−2 for HER and OER in alkaline media, respectively, and demonstrates excellent stability over a 10 h test. This research provides valuable insights into the development of advanced materials capable of efficiently performing both HER and OER processes, paving the way for potential applications in sustainable energy technologies.